Variables of Occupational Induced Stress and Coping styles among Teachers in Selected Special and Regular Primary Schools in Cross River State, Nigeria - Eke, Vitalis Ugochukwu; Laetitia, Anakwue Anthonia; Dasel, Nanjuwan Josephine; Obioma, Ajah Mabel; Atah, Unimuke Gregory (Richtmann Publishing, 2020)
The study investigated the variables of occupational induced stress and coping styles among Teachers in selected Special and Regular Primary Schools in Cross River State, Nigeria. The study adopted descriptive research design and specifically used descriptive statistics to analyze the data. In a bid to arrive at the sample, multistage sampling procedure and purposive sampling techniques were used. 100 teachers therefore formed the sample that was purposively drawn from special and regular primary schools in Cross River State, Nigeria. Two instruments were used for the study named respectively: Teachers’ Occupational induced stress Questionnaire (TOISQ) and Teachers’ Coping styles Questionnaire (TCSQ). These are structured Questionnaire constructed by the researchers. They adopted modified likert scale with four response options to the ten item-statement respectively. The Instruments were face and content validated by three experts. Cronbach Alfa was used in each case to establish the reliability coefficient. The respective reliability coefficient was .83 and .81. The result and findings from the study disclosed occupational induced stress to include among others: heavy work loads, time pressure, technical demanding skills, insufficient teaching materials while the coping styles among others were practicing classroom management and associating with people for emotional stability. The recommendations among others include exposing the teachers in training and serving teachers to occupational induced stress and the coping strategies.